2016
DOI: 10.1080/09687599.2016.1256273
|View full text |Cite
|
Sign up to set email alerts
|

Disability and social justice

Abstract: This article explores the significance of disability for social justice, using Nancy Fraser's theory of justice as a guideline. The article argues that the disability perspective is essential for understanding and promoting social justice, although it is often disregarded by critical thinkers and social activists. The article looks at three prominent strategies for achieving social justice under conditions of capitalism: economically, by decommodifying labour; culturally, by deconstructing self-sufficiency; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 36 publications
0
29
0
1
Order By: Relevance
“…The recognition of human dignity comprises a central principle of social justice (Honneth 2004). According to Mladenov (2016), a strategy of redistribution could be either affirmative or transformative: the transformative strategy is appealing to our writing centre project. Redistribution, according to Mladenov (2016), could promote surface reallocations of economic outputs without touching the underlying structures that generate economic inequality, or it could attempt deep-level economic restructuring.…”
Section: The Writing Centre and Dialoguesmentioning
confidence: 99%
“…The recognition of human dignity comprises a central principle of social justice (Honneth 2004). According to Mladenov (2016), a strategy of redistribution could be either affirmative or transformative: the transformative strategy is appealing to our writing centre project. Redistribution, according to Mladenov (2016), could promote surface reallocations of economic outputs without touching the underlying structures that generate economic inequality, or it could attempt deep-level economic restructuring.…”
Section: The Writing Centre and Dialoguesmentioning
confidence: 99%
“…Yet autism is used by Crary as a way to condemn television that, according to a study quoted by Crary (2014: 86), 'might have a catastrophic physical impact on the developing human being … it could produce extreme, permanent impairments in the acquisition of language and in the capacity for social interaction'. In this account, autism is a pathology created by 24/7 capitalism rather than an impediment to its total instrumentalisation of life, as sleep is argued to be (Mladenov, 2016(Mladenov, : 1227. Such an individualised and pathologised rendering of disability has prevented Crary from engaging with the perspective championed by disability studies.…”
Section: Himselfmentioning
confidence: 99%
“…But how exactly could disability generate immanent resistance to performativity? In my previous work (Mladenov, 2016(Mladenov, , 2017, I have suggested that one of the ways of reversing the creeping performative dystopia of contemporary capitalism is by rescuing the disability category from its neoliberal effacement. Such countermovement requires liberalising disability assessment so that people who seek disability support have greater access to it (Mladenov, 2016(Mladenov, : 1231.…”
Section: Conclusion: Possibilities Of Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The theory proposed by critical theorist Nancy Fraser can be very fruitful for disability policy analyses (for analyses in the Western capitalist context: Dodd, 2016;Knight, 2015;Mladenov, 2016; for analyses in the global context: Soldatic, 2013;Soldatic & Grech, 2014; for care policy: Swaton, 2017; for personal assistance: Mladenov, 2012;Mladenov, Owens, & Cribb, 2015;Owens, Mladenov, & Cribb, 2017). According to Fraser (2003), there are generally two dimensions of social justice: recognition justice and redistributive justice.…”
Section: The Bivalent Nature Of Social Justicementioning
confidence: 99%